Էջերի իրանահայության պատմությունից XIX դարում - Բայբուրդյան, Վահան («Զանգակ - 97»)
Armcnians havc lived in Iran since ancient times. However, a well-organized Armcnian Community with national and rehgious institutions emerged only in the 17th century. Düring the 19th century, Armenians continued to play an important role in the social, polilical, commercial. economic, and cultural life of Iran. Armeniens have made a vast contribution to the modernization and westernization of Iran.
Keywords: Պատմություն; Ազգագրություն